UKRAINIAN DIASPORA IN TRANSCAUCASIAN REGION: DYNAMICS OF NUMBER, FEATURES OF RESETLEMENT - Зубик, А. І. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
The article analyzes the causes of creation, dynamics of population and characteristics of settlement of the Ukrainian diaspora in Armenia, Azerbaijan and Georgia. The results of population census in Armenia, Azerbaijan and Georgia at the beginning of 2010s are the informational base of research. The number of the Ukrainian diaspora is established according to ethnic criteria in programs of censuses. According to the results of population censuses it was established that from the end of 80th years of XX century the Ukrainian diaspora had significantly decreased. Thus, in the structure of the Ukrainian diaspora the share of region increased by more than half: from 0.95% (in 1989) to 0.41 (XXI cen.). The average annual number decrease of the Ukrainian diaspora is higher in comparison with the countries of the former Soviet Union. The Ukrainian diaspora in the region is highly urbanized, the Ukrainians mainly living in the capital. Such settlement of the Ukrainian diaspora causes reasons of its appearance; the Ukrainians and the Russians constituted the so-called "Technological elite" and concentrated in large industrial and research centers in these countries. At the present stage of urbanization the Ukrainian diaspora seek work in cities, study and so on. It is noted that the Ukrainian diaspora live in complicated ethnic, linguistic and religious environments, that lead to isolation of the Ukrainian diaspora. Thus, it can be argued that the Ukrainian diasporas in this region form the hub of the diaspora. However, on the basis of differences with ethnos title the Ukrainians integrate in the more numerous environment of the Russian diaspora. The collapse of the Soviet Union has led to significant geopolitical changes in the region, embodied in military conflicts, the decline of the economy and as a result re-emigration to Ukraine or other countries.